1996
DOI: 10.1302/0301-620x.78b3.0780441
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Analysis of the Kinematic Stabilizer Total Knee Replacement

Abstract: The Kinematic Stabilizer is a posterior-cruciatesubstituting design of total knee replacement. We have reviewed 109 primary total knee replacements in 95 patients at a mean follow-up time of 12.7 years (10 to 14). We used survival analysis with failure defined as revision of the implant. This gave a cumulative survival rate of 95% (95% CI± 5%) at ten years and 87% (± 10%) at 13 years.These results from an independent centre confirm the value of an established design of cemented total knee replacement and quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 8 publications
2
36
0
1
Order By: Relevance
“…Early survival studies of UKA demonstrated revision rates of 15% to 28% [23,34,44]. More recent articles report substantial increases in survival, with midterm survivorship for UKA of 84% to 98% (Table 1) [10,12,14,19,39,40,42,46,48,[57][58][59][60][61]. O'Rourke et al [43] followed by Price and Svard [49] documented long-term survival rates of UKA at 20 years of 84% and 91%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Early survival studies of UKA demonstrated revision rates of 15% to 28% [23,34,44]. More recent articles report substantial increases in survival, with midterm survivorship for UKA of 84% to 98% (Table 1) [10,12,14,19,39,40,42,46,48,[57][58][59][60][61]. O'Rourke et al [43] followed by Price and Svard [49] documented long-term survival rates of UKA at 20 years of 84% and 91%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many survival analyses of TKR include a number of patients lost to follow-up ranging from 3% to 13% of the initial cohort. [13][14][15][16][17] The reported cumulative survival rates in these series may be an overestimation of the true survival rate. 21 Implant survival data for patients who have died are often not included and some of these prostheses may have been revised before death.…”
Section: Discussionmentioning
confidence: 99%
“…Other published survival analyses include only limited data concerning clinical outcome. In these reports either clinical assessment is collected and not reported, 22 postoperative scores are reported but not compared with preoperative scores, 14,17,23 or only preoperative scores are included. 13,16 The number of implants with clinical assessment at ten years in our series is only 16% of the original cohort and therefore represents only a minor indication of the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These differences carry implications for guiding care and resource allocation. New approaches to capturing the diagnoses and procedures that physicians and hospitals code as part of the billing process, such as the those used by the Nationwide Inpatients Sample (NIS), allow for larger-scale evaluations of the epidemiology of revision total joint arthroplasties than previously could be performed [13,14,17,37,51,56]. Prior studies [7,8] have been done that investigated the revised coding scheme in a national sample [1] to more clearly identify the indications for revision, procedure frequencies, and degree of adoption of the new diagnosis and procedure codes.…”
Section: Introductionmentioning
confidence: 99%